2022
DOI: 10.3390/cells11243999
|View full text |Cite
|
Sign up to set email alerts
|

Novel Tuning of PMMA Orthopedic Bone Cement Using TBB Initiator: Effect of Bone Cement Extracts on Bioactivity of Osteoblasts and Osteoclasts

Abstract: Bone cement containing benzoyl peroxide (BPO) as a polymerization initiator are commonly used to fix orthopedic metal implants. However, toxic complications caused by bone cement are a clinically significant problem. Poly (methyl methacrylate) tri-n-butylborane (PMMA-TBB), a newly developed material containing TBB as a polymerization initiator, was found to be more biocompatible than conventional PMMA-BPO bone cements due to reduced free radical generation during polymerization. However, free radicals might no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Thus, cells could not survive as in the previously reported experiment, due to differences in the resistance of the cells to the material components and to the effects of the different methods of eluting the residual components. Chromatographic analysis is necessary to measure the elution of components over time [ 18 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, cells could not survive as in the previously reported experiment, due to differences in the resistance of the cells to the material components and to the effects of the different methods of eluting the residual components. Chromatographic analysis is necessary to measure the elution of components over time [ 18 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In light of other potential methods to improve composite materials, N-acetyl cysteine, a precursor of glutathione, the most potent antioxidant in the body, effectively scavenges polymerization radicals and neutralizes chemicals that cause oxidative stress [ 9 , 10 , 15 , 17 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Tri-n-butyl borane, a polymerization initiator, also reduces cytotoxicity, due to the suppressive role of polymerization radicals [ 11 , 13 , 14 , 18 , 33 , 72 ]. These data provide design rules for the use of monomers and initiators to create novel composite materials with higher biocompatibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first study to evaluat influence of provisional materials on cells with different phases of cell settlement. Some studies have shown that material compositions such as monomers, polym zation initiators, and filler particles influence their cytotoxicity [48][49][50][51][52][53][54]. It is known unreacted monomers exert critical biological effects on cells [15,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were fixed in 10% formalin and stained with the fluorescent dye rhodamine phalloidin (actin filament, red color; Molecular Probes, Eugene, OR) and 4 ,6-diamidino-2phenylindole (DAPI) (nuclear, blue color; Abcam, Cambridge, UK). Fixing with formalin was proven effective, particularly for immunostaining combined with fluorescent dye in our previous studies [52,118,119].…”
Section: Number Of Attached and Propagated Cells Cell Attachment Assa...mentioning
confidence: 99%